Krüppel-like factors in mitochondrial quality control - Zhang, M. Y.; Zhang, H.; Yao, Y. M.; Yang, D. W. (Frontiers in Physiology, 2025)
Krüppel-like factors (KLFs) are a group of transcription factors characterized by conserved zinc finger domains in the C-terminus, which are critically involved in basic cellular processes, including growth, differentiation, apoptosis, and angiogenesis, and play important roles in many pathophysiological responses. Mitochondrial homeostasis relies on a coordinated mitochondrial quality control system, which maintains the number and morphological stability and coordinates mitochondrial physiological functions through renewal and self-clearance. In this paper, we review the current advances of KLFs in mitochondrial quality control (MQC), including the potential roles and regulatory mechanisms in mitochondrial biogenesis, mitochondrial fusion/fission, mitophagy and mitochondrial unfolded protein response. We also introduce the specific pharmacological modulation of KLFs, expecting to transforming basic research achievements and providing the possibility of targeted therapy for KLFs.